Efektivitas Model Found Poetry terhadap Keterampilan Menulis Puisi Siswa Kelas XI SMAN 6 Karawang: The Effectiveness of the Found Poetry Model on Poetry Writing Skills: A Study on Grade XI Students of SMAN 6 Karawang - Maria Ulfa; Een Nur Hasanah; Sahlan Mujtaba (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to determine the effectiveness of the Found Poetry model on the poetry writing skills of Grade XI students at SMAN 6 Karawang in the 2024/2025 academic year. This research employed a quantitative approach using a posttest-only control group design. The sample consisted of two classes: an experimental class treated with the Found Poetry model and a control class using conventional learning. The instrument used was a poetry writing test based on the assessment aspects proposed by Waluyo (2003), namely diction, imagery, figurative language, rhyme/rhythm, typography, theme, feeling, tone, message, and unity of the poem. The analysis results showed a significant difference between the posttest scores of the experimental and control classes. The average posttest score of the experimental class was 35.70, while the control class scored 23.67. The t-test results showed a significance level of 0.000 < 0.05, indicating a positive influence of the Found Poetry model on students' poetry writing skills. Thus, Found Poetry is proven effective and can serve as an alternative method for teaching poetry writing at the senior high school level.